THE EXPLORATION OF SHADOW AND ANIMA IN OTTO ANDERSON'S INDIVIDUATION PROCESS IN A MAN CALLED OTTO FILM (2022) - Davina Anandira Kuswantari (Journal of Language, Literature and Teaching, 2026)
The study explores the role of Shadow and Anima archetypes in Otto Anderson's individuation process in the film A Man Called Otto (2022). It seeks to understand how Otto's Shadow and his Anima are expressed in his daily life with his neighbors, and how his individuation is expressed as a result of integrating his Shadow and Anima. The study is based on Carl Jung's analytical psychology and uses the concepts of archetypes (Shadow and Anima) as the primary theoretical framework. The study is qualitative and uses the Jungian analysis of film as a method of interpreting the film narrative, dialogue, and monologue as primary data. Secondary data sources consist of scholarly literature on Jungian theory and film studies. Data were gathered by repeated watching, close reading of the subtitles, screenshots, and thematic coding of scenes depicting the Shadow projection, the Anima influence, and the stages of individuation, and then analyzed by mapping the data to Jung's concepts. The findings indicate that Otto's Shadow, which is based on traumatic events, manifests in several ways including suicide attempts, unintegrated grief, denial of reality, and rudeness toward others. In contrast, his Anima is activated first by Marisol and the caring neighborhood community, which gradually restores Otto's ability to empathize, nurture, and take responsibility for relationships. In general, the study demonstrates that individuation for Otto is not about forgetting loss, but rather is about the integration of his Shadow and his Anima into a unified sense of Self. The discovery highlights the psychological complexity of characters in modern films, revealing the potential of Jungian analysis in exploring the unconscious mind within popular film genres.